Selective and effective adsorption of Hg(II) from aqueous solution over wide pH range by thiol functionalized magnetic carbon nanotubes. (July 2019) - Fan, Lu; Zhou, Anlan; Zhong, Linrui; Zhang, Zheng; Liu, Yong
Abstract: In this study, a novel adsorbent thiol functionalized magnetic carbon nanotubes (CNTs-SH@Fe3 O4 ) was synthesized to overcome somewhat existing difficulties during the Hg(II) adsorption process, including low efficiency and selectivity, narrow feasible pH range and difficult to separate and reuse. The Hg(II) adsorption performance of CNTs-SH@Fe3 O4 was evaluated using batch experiment and its physiochemical properties were investigated by characterization techniques. The batch experiment results showed that the prepared CNTs-SH@Fe3 O4 maintained high Hg(II) adsorption efficiency (>98%) over wide pH range from 3 to 11. The selective adsorption of Hg(II) by CNTs-SH@Fe3 O4 was achieved with the coexistence of Cu(II), Mg(II) or Zn(II) ions, in which adsorbate matrix Hg(II) removal efficiency of 81.39%, 89.36% and 95.52% was obtained, respectively. CNTs-SH@Fe3 O4 kept high Hg(II) removal efficiency (>80%) and good magnetic property (Ms value > 21 emg g −1 ) after five cycles of adsorption/regeneration. The Hg(II) adsorption kinetics could be better described by pseudo-second-order kinetic model. Freundlich model showed higher correlation coefficient in adsorption isotherms study, and the calculated maximum adsorption capacity was 172.4 mg g −1 . Thermodynamic study suggested that the adsorption process was exothermic in nature. Surface adsorption, complex adsorption and reduction adsorption were all contributed to the removal of Hg(II) using CNTs-SH@Fe3 O4 . Highlights: CNTs-SH@Fe3 O4 was synthesized and employed for Hg(II) adsorption. CNTs-SH@Fe3 O4 showed excellent Hg(II) removal efficiency in wide pH range from 3 to 11. CNTs-SH@Fe3 O4 showed high selectivity toward Hg(II) in binary ion matrices. CNTs-SH@Fe3 O4 kept good Hg(II) removal and magnetic property after 5 cycles of regeneration.